Using The "Return on Investment" Strategy to Sustain Logistic Supply Provider Toward Indonesia's Logistic Policy - Riska Rahayu; Eko Priyo Purnomo; Ajree Ducol Malawani (Journal of Government and Civil Society, 2020)
The purpose of this paper is to analyze the strategies carried out by Supply Logistics in the supply chain using supply chain management analysis also to facilitate the logistics chain in Indonesia. SCM previous research did not have a studio that discussed supply chain by manager logistics strategies and what methods they used to maintain logistics inventory. The research methodologists carried out using qualitative adopted an exploratory data analysis (EDA) approach to qualitative research that defines and explains the issues obtained. Open coding was applied to find issues the most dominant and was used to classify the number of issues related to the data and visualized into word cloud obtained using NVIVO 12 Plus. Data were collected from Indonesia logistic supply chain sites. The findings of this article is ROI (Return on Investments) is a logistics strategy will support for reducing the investment costs by logistics provider company. Analysis of supply chain management can develop better emphasizes logistic chains in Indonesia.Dalam artikel ini memiliki tujuan untuk menganalisis strategi dalam tantangan penyaluran logistic yang merata. Dengan menggunakan analisis sistem Supply Chain Management (SCM) yang akan memetakan strategi apa yang dilakukan Indonesia dalam tantang penyaluran logistik. Studi SCM terdahulu telah banyak adanya, namun tidak berfokus pada penyaluran logistik dalam strateginya untuk menjaga keseimbangan rantai pasokan logistik. Penelitian ini menggunakan metode kualitatif yang mengadopisi pendekatan Exploratory Data Ananlysis (EDA) untuk menjelaskan dan mendefinisikan temuan masalah. Open Coding dikukan untuk menemukan topik dan mengklasifikasikan yang dominan dan memvisualisasikannya menjadi word cloud dengan NVIVO 12 Plus. Data diperoleh dari website logistic supply chain Indonesia. Temuan dari artikel ini adalah Return on Investments (ROI) adalah strategi yang digunakan dalam strategi logistik yang akan membantu mengurangi dengan melakukan  investasi dari beberapa perusahaan penyaluran logistik. Analisis SCM dalam penyaluran logistik dapat mengembangan tekanan tantangan logistik di Indonesia.